The Influence of Various Varieties and Various Liquid Organic Fertilizer to Papaya Plant Seed Growth (Carica papaya L.) - Primadiyanti Arsela (Agrifor : Jurnal Ilmu Pertanian dan Kehutanan, 2018)
The main goal of the study was to determine the effect of various  Papaya varieties and liquid organic fertilizer on the growth of Papaya seedlings(Carica papaya L.). The research used Randomized Block Design (RAK) with two factors factorial experimental. The first factor is Variety (V) consists of 3 Papaya varieties: v1= bangkok , v2= red lady , v3= sunrise. The second factor is Fertilizer (C) consists of 3 brands: c1= Em4 10 ml, c2= Green Tonic 10ml, c3= Nasa 10ml. This study has 3 treatment levels consisting of 9 combinations and  repeated 3 times. The results of the study are treatment of various varieties (V) had significant effect on stem diameter and root number. The effect of various liquid organic fertilizer (C) had significant effect on the root length parameters. The interaction all treatment had a very significant effect on the root length and the root number parameter.